A novel facilitated negative-pressure wound therapy for thoracic incision infection after esophagectomy - Wang, Zhi-Tian; Cao, Jin-Lin; Yuan, Ping; Wang, Lu-Ming; He, Zhe-Hao; Lv, Wang; Hu, Jian (Journal of Thoracic Disease, 2017)
Background: Negative-pressure wound therapy (NPWT) is the therapeutic management of traumatic soft-tissue wounds and infections. The efficacy of NPWT in the treatment of thoracic incision infection is unclear. We assess the effectiveness and safety of a novel facilitated NPWT for thoracic incision infection after esophagectomy. Methods: Between Jan. 2013 and Mar. 2016, 380 patients underwent open esophagectomy in our department. Forty-five patients with thoracic incision infection were retrospectively reviewed. Of these patients, 25 were treated with NPWT and 20 patients were treated with open wound dressing. The patients’ clinical demographic data, postoperative outcomes and wound treatment cost are reviewed. Results: The thoracic incision infection rate was 11.8%. All of the incision infections were cured in the hospital or on an outpatient basis. No allergic reactions or other side effects occurred with NPWT. Although the patients who were treated with NPWT did not have a significantly shorter postoperative hospital stay than those treated with open wound dressing (P=0.092), the use of NPWT therapy for thoracic incision infection led to a shorter wound healing times (13 vs. 20 days; P=0.004) and a lower wound treatment cost (P=0.020). Conclusions: Thoracic incision infection is a common complication of esophagectomy. NPWT is a safe and effective therapeutic management for thoracic incision infection that is associated with shortened wound healing times and reduced wound treatment costs than traditional open wound treatment.